Analysis and Design of PT KDA Langling Cooperative System Through Web-based Savings and Loan Transformation Technology - Ade Agung; Widja Yanto; Dafit Afianto (TIERS Information Technology Journal, 2023)
PT KDA Langling Cooperative, as an economic enterprise dedicated to the interests of villagers and employees, is located in Langling Village RT 15, PT KDA Langling Sinarmas Housing. In order to manage savings and loans, the current system faces significant obstacles because it has not used computer technology. Recording is still done manually in books, causing delays in data collection and the potential for loss or damage to data in the archive. This research aims to analyze the current system, with a focus on fixing these problems. The solution is to design a web-based savings and loan information system that will optimize the efficiency and accuracy of data. The method that will be used by the author is literature review, data collection and using the waterfall model with the stages of the process of analyzing needs, design, implementation, testing and maintenance, using the PHP programming language and MySQL DBMS, UML and Usecase diagram. So that this research produces an integrated system that provides convenience for users in savings and loan activities and presents web-based financial information.